Ambrisentan: a review of its use in pulmonary arterial hypertension. (June 2017) - Rivera-Lebron, Belinda N.; Risbano, Michael G.
Pulmonary arterial hypertension (PAH) is a progressive disease defined by an elevation in pulmonary arterial pressure that can lead to right heart failure and death. Ambrisentan is a selective endothelin receptor antagonist approved for the treatment of idiopathic, heritable PAH and connective tissue disease-associated PAH. Ambrisentan has been shown to improve exercise capacity and hemodynamics with an acceptable side-effect profile. It has also proven to be safely used in combination with other PAH-specific medications, especially with phosphodiesterase-5 inhibitors. In the recent randomized trial, AMBITION, it was shown that upfront combination therapy of ambrisentan and tadalafil significantly decreased the risk of clinical failure compared with monotherapy. This review describes the drug profile of ambrisentan and its safety and efficacy in the treatment of PAH.